Analysis of rectangular waveguide with corrugated broad wall - Naidenko, Viktor; Shumakov, Denis (Видавництво Львівської політехніки, 2012)
Analysis of rectangular waveguide with corrugated broad wall is performed based on Galerkin method in conjunction with Floquet’s theorem. Dispersion, power, energy, modal field distribution of the structure are calculated.
Keywords: Galerkin method; Floquet’s theorem; dispersion